SURVEI PEMAHAMAN SISWA TENTANG GAYA BELAJAR DI SMP NEGERI 8 PALANGKA RAYA - Sitorus, Sabar Halimah; Pangestie, Esty Pan; Apriatama, Dony (Counseling For All : Jurnal Bimbingan dan Konseling, 2023)
Learning style is a person's way of absorbing and obtaining information in learning, but many students still do not know the learning style that is in them. This study aims to determine students' understanding of learning styles and to find out the learning styles (Visual, Audio, Kinesthetic) of students at SMP Negeri 8 Palangka Raya. This type of research is quantitative research with a survey method with the Purposive Sampling technique. The population in this study were all students of class VIII with a total of 351 students with 88 students as a sample member. This research was conducted in October 2022. Data collection was carried out using a questionnaire which was distributed via the Google form. Based on the research results, it is known that students' understanding of learning styles is in the "very good" category (25.98) and the results show that the audio type student learning style has a percentage of 37.5%, kinesthetic type students have a percentage of 34% and visual type students has a percentage of 28.5%. This shows that the level of students' understanding of learning styles at SMP Negeri 8 Palangka Raya is good and learning styles are dominated by audio learning styles with a percentage of 37.5%.